Adaptive control of seam tracking through progressive HAZ and weld pool penetration using thickness measurement - Baharin, Iskandar; Mir sadehgi, Bahram H.
A mathematical model for predictive/adaptive control of weld bead penetration and seam tracking in Tungsten Inert Gas Welding as an approach to process control of robotic GTAW has been developed. Weld process parameters such as: base current and time, pulse current and time, electrode tip to workpiece distance, filler traveling speed, torch traveling speed and workpiece thickness has been used for finding the equations which describing interrelationship between the aforementioned variables and penetration depth as well as bead width. The calculation of these equations developed from the statistical regression analysis of 80 welds deposited using various combinations of welding parameters. For monitoring of workpiece thickness variations, an ultrasonic device has been used. In order to accurate control of weld bead width and also seam tracking, a CCD camera was used. The results show that the misalignment or asymmetry of progressive HAZ in adjacent to weld puddle is detectable and can be used for control of trajectory. Scanning of certain area of captured image in front of weld puddle decreases the data processing time drastically.